Some Vertebrate Pests in the Rajasthan Desert - Prakash, Ishwar (Indian Forester, 1964)
The important vertebrate pests found in the desert of Rajasthan have been listed and an idea has been given about their relative numbers and geographical distribution. The degree of depradation by these vertebrate pests on the desert vegetation has been discussed. The management practices for some vertebrate pest have been given. A method to control the rodents in the field has been explained.